Modular and non-invasive distributed memory parallelization - Gonçalves, Rui (2012)
This paper presents an aspect-oriented library to support parallelization of Java applications for distributed memory environments, using a message-passing approach. The library was implemented using AspectJ language, and aims to provide a set of mechanisms to make easier to parallelize applications, as well as to solve well known problems of parallelization, such as lack of modularity and reusability. We compare the advantages of this method over the traditional approach, and we discuss differences to recent approaches that address the same problem. Results show benefits over other approaches, and, in most of cases, a competitive performance.